Sex in the brain: hormones and sex differences - Marrocco, Jordan; McEwen, Bruce S. (Dialogues in clinical neuroscience, 2016)
Contrary to popular belief, sex hormones act throughout the entire brain of both males and females via both genomic and nongenomic receptors. Many neural and behavioral functions are affected by estrogens, including mood, cognitive function, blood pressure regulation, motor coordination, pain, and opioid sensitivity. Subtle sex differences exist for many of these functions that are developmentally programmed by hormones and by not yet precisely defined genetic factors, including the mitochondrial genome. These sex differences, and responses to sex hormones in brain regions and upon functions not previously regarded as subject to such differences, indicate that we are entering a new era in our ability to understand and appreciate the diversity of gender-related behaviors and brain functions.